THREE HUMAN STR LOCI WITH THE MOST VARIED GENOTYPE - Hidayat (NIM 205 06 038), Karina
ABSTRACT: Perpetrators usually use false identities in their crimes, which encumbers the investigators to reveal their true identity. In other hand, the individual identity based on human genetic code is unique, cannot be manipulated, and can represent their true identity. In this case, the individual identity can be determined using the polymorphism patterns of both nuclear and mitochondrial DNAs. In routine forensic analysis the usage of mtDNA patterns as individual identity has several advantages such as: its retrievable nature even in highly degraded samples and the presence of hypervariable region (D-Loop). However, mtDNA will exhibit the same patterns for individual in the same maternal lineage. The polymorphism patterns of nuclear DNA that generally used for identification are short tandem repeat. Short tandem repeat (STR) loci are polymorphic regions found in the genome that are used as genetic markers for human identity testing. In order to perform an identity testing based on STR analysis, thirteen STR loci are needed to distinguish among individuals, including relatives as close as siblings. Despite of its high discriminating nature, STR analysis has several weaknesses as follows, the thirteen STR loci are often inaccessible due to their presence in a very limited number of nDNA copies, and there are only two copies per cell, which leads to a low probability to find undegraded nuclear DNA in highly degraded samples. In addition, it requires a high technology capillary electrophoresis device, which makes it difficult to be applied in a modest forensic laboratory. The aim of this research is to obtain a few STR loci among thirteen loci that can be used as routines in individual discrimination with the same mtDNA patterns. This research is divided into two main following parts, the in silico approach and the experimental part. The in silico study consists of downloading STR pattern from public database, grouping allele series per locus, and sorting the STR loci based on the genotype variation. The verification of selected loci was carried out by PCR method and the result was analyzed by gel agarose electrophoresis. The STR patterns were downloaded from the official site of European Network of Forensic Science Institute (ENFSI), and grouped by allele series per locus with Microsoft Excel. Furthermore, the genotype variation was counted and loci with high genotype variation were used in STR profile typing of two individual with the same mtDNA patterns. The primers that were used in this analysis were synthesized based on Powerplex 1.1 primers from Promega. The PCR amplification results were analyzed using gel agarose electrophoresis. The nine STR loci from 1172 sample that has been collected from public database are D3S1358, vWA, FGA, D8S1179, D21S11, D18S51, D5S818, D13S317, and D7S820. The grouping and calculation results of allele series showed that six loci had 9-12 series of allele, while three loci had 21-33 series of allele. FGA was the most varied locus which had 113 genotypes, followed by D21S11 and D18S51 with 87 genotypes each, while D8S1179 was at the third position with 44 genotypes. Three loci that were selected from varied genotype loci are D8S1179, D21S111, and FGA. The synthesis of primers and the amplification of the three selected loci showed positive results. The most varied genotype loci are selected in order to find a loci which have high power of discrimination therefore the personal identity can be determined by combining the hypervariable mtDNA profile with the selected STR loci patterns. The smaller number of STR loci are used in this analysis due to the efficiency reason. FGA is chosen among the other nine loci because it is the most varied genotype locus, thereafter D21S111 was chosen because its theoretical genotype was higher than D18S51, while D8S1179 because the genotype variation was at the third place. The selected loci not only have high number of observed genotype variation but also theoretical genotype variation. Thus, it is expected with the high number of theoretical genotype that there is still another genotype outside of the observed data population that enriches its variety. High genotype variation will enhance the power to discriminate person in the same maternal lineage. We hope that combination between the three STR loci profile and mtDNA profile can distinguish individual with the same mtDNA pattern.